URGENSI PENDIDIKAN MODERASI BERAGAMA PADA GENERASI DIGITAL NATIVE - Taufiq Budi Sholihin; Luluk Zidan Muizzuddin; Madkha Madda Bila Sahiil; Muhammad Ridwan Afifuddin (FAJAR Jurnal Pendidikan Islam, 2024)
Religious moderation is one of the government's steps in stemming the negative currents of the times that are accelerating, the digital nativ generation is one of the generations that get the most impact from the development of this era;  this study aims to determine the urgency of religious moderation education in the digital native generation. The method used in this research is a qualitative method with a library research design, this technique The data collection procedure is carried out by understanding and studying theories from various literatures related to the research. The result of this study is that the digital native generation who use social media get more impact than the digital native generation who do not use social media.